Mobile phones in conflicts of financial intermediation - Simplice A. Asongu; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2015)
To the best our knowledge, in the first empirical macroeconomic examination of the nexus between financial intermediation and mobile phones, Asongu employs two conflicting financial system definitions in the assessment of how mobile phones have stimulated financial development in Africa. Within the framework of the dominant International Monetary Fund's International Financial Statistics (2008) definition, mobile phones are established to be negatively associated with financial intermediary dynamics of depth, activity and size. Conversely, when the previously neglected informal financial sector is integrated into the conception, definition and measurement of the financial system, mobile phones are positively (negatively) correlated with the informal (formal) financial intermediation sector. The empirical evidence is based on 52 African countries. Causality in the established linkages has been confirmed in subsequent studies by the same author. At least three policy implications derive from the findings. First, the role of informal financial intermediation is increasing to the detriment of formal financial mechanisms. Second, in order to capture the positive effect of mobile phones on finance, it is imperative to integrate the missing informal financial sector component into the IMF definition of the financial system. Third, it is a wake-up call for more scholarly research on: (i) macroeconomic financial development implications of mobile phone penetration and (ii) monetary policy instruments in the face of burgeoning 'mobile phone'-oriented financial intermediation.
Keywords: E00; G20; L96; O17; O33; 330; Banking; Mobile Phones; Shadow Economy; Financial Development; Africa